QUALITY ADMINISTRATION MODEL OF WORLD CLASS SECONDARY SCHOOLS, BANGKOK METROPOLITAN AREA UNDER THE JURISDICTION OF BASIC EDUCATION INSTITUTION COMMISSION OFFICE - Thanapatwautthikul, Kridtiya; Ninseangrat, Navin (Journal of MCU Nakhondhat, 2021)
The objectives of this research were 1) to create and develop quality administration model of world class secondary schools and 2) to investigate suitability and feasibility of quality administration model of world class secondary schools, Bangkok metropolitan area under the jurisdiction of basic education institution commission office. This research was quantitative method research. The conceptual framework of this research was studied for learner development activity management according to Education department. The population consisted of 550 educational institution administrators and assistants of world class secondary schools, Bangkok metropolitan area under the jurisdiction of basic education institution commission office. The sample was 220 people determined by purposive random sampling. The instrument used in the study were two questionnaires that the first was about statis of respondents and the second was achievement visual results of quality administration model of world class secondary schools, Bangkok metropolitan area under the jurisdiction of basic education institution commission office and depth interview with 10 experts and investigate suitability and feasibility was by 5 specialists. Statistics used for data analysis were frequency, percentage, mean and standard deviation. The research results revealed that: 1) quality administration model of world class secondary schools, Bangkok metropolitan area as a whole was at much level. When considering each aspect found that all aspects were at much level, in descending order as follows by 1) the fifth group; personnel focusing in environmental of personnel aspect 2) the seventh group; result, work system management to school development through learning organization aspect.3) the third group; customer focusing in opinion of customer aspect. 4) the sixth group; performance focusing in work system aspect and 5) the first group; performance focusing in work process aspect. 2) Investigate suitability and feasibility results of quality administration model of world class secondary schools, Bangkok metropolitan area under the jurisdiction of basic education institution commission office as a whole was at much level, when considering each aspect found that 4 aspects were at much level in descending order as follows by 1) academic excellence 2) design thinking 3) creative product 4) communicate less than 2 languages and 5) world social responsibility.